Synergistic Regulatory Effect of Inhibin and Anti-Müllerian Hormone on Fertility of Mice - Yu, Xue; Qiao, Tong; Hua, Liping; Liu, Shuanghang; Zhao, Xinzhe; Lv, Ce; Zhao, Xuhong; Wang, Jing; Han, Li; Yang, Liguo; Liang, Aixin (Frontiers in Veterinary Science, 2021)
Inhibin (INH) and Anti-Müllerian hormone (AMH) are essential in ovarian folliculogenesis and play an inhibitory role in mammalian fertility. However, the interactive effect of INH and AMH on the animal reproduction remains unknown. This study aimed to determine the possible interaction and synergy between INH and AMH in steroidogenesis by primary granulosa cells, and investigate their synergistic effect on fertility in mice. In in vitro granulosa cell culture system, we found that the treatment of either INHA or AMH had no significant effect on basal estradiol and progesterone production, whereas, both significantly attenuated FSH-induced steroid hormone secretion. Importantly, combined treatment with INHA and AMH showed additive inhibitory effect on FSH-induced estradiol and progesterone production, accompanying a significant downregulation in the expression of FSH-stimulated CYP19A1, HSD3B, CYP11A1, StAR transcripts. The interrelationship of INH and AMH combinations was further investigated through active immune neutralization strategy. Female mice were immunized against INH and AMH eukaryotic expression plasmids, and the litter size was recorded after successfully mating. We observed that both INH and AMH plasmids were able to induce either anti-AMH or anti-INH antibodies in the immunized mice. In comparison to the control group, co-immunization with INH and AMH plasmids induced higher levels of estradiol, resulting in more litter size. Moreover, there was no significant difference on offspring’s weight between each group. Collectively, the results of the present study suggest that INH and AMH have synergistic effect in regulating steroidogenesis and the litter size in mice.